Early Marriage Problems in Indonesia - Angkasa, Aghnat Bintang (Universitas Negeri Semarang, 2021)
Marriage in Indonesia is based or regulated in Act No. 1 of 1974 concerning Marriage. In Chapter 2, article 7, paragraph 1 reads